2017
DOI: 10.3390/nu9121361
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Dietary Fiber and Gut Health: Comparing the in Vitro Fermentations of Beta-Glucan, Inulin and Xylooligosaccharide

Abstract: Prebiotic dietary fiber supplements are commonly consumed to help meet fiber recommendations and improve gastrointestinal health by stimulating beneficial bacteria and the production of short-chain fatty acids (SCFAs), molecules beneficial to host health. The objective of this research project was to compare potential prebiotic effects and fermentability of five commonly consumed fibers using an in vitro fermentation system measuring changes in fecal microbiota, total gas production and formation of common SCF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(119 citation statements)
references
References 64 publications
11
107
0
1
Order By: Relevance
“…As expected, larger volumes of CO 2 and H 2 were obtained from the lactulose and XOS fermentation when comparing to the blank. Carlson et al (2017) and Buruiana et al (2017) reported the same trend in gas production using in vitro models with human fecal inoculum and XOS obtained from corn stover. Methane was not detected for both donors' samples.…”
Section: Gas Productionmentioning
confidence: 58%
See 1 more Smart Citation
“…As expected, larger volumes of CO 2 and H 2 were obtained from the lactulose and XOS fermentation when comparing to the blank. Carlson et al (2017) and Buruiana et al (2017) reported the same trend in gas production using in vitro models with human fecal inoculum and XOS obtained from corn stover. Methane was not detected for both donors' samples.…”
Section: Gas Productionmentioning
confidence: 58%
“…Moreover, in in vivo models, the produced SCFAs are rapidly absorbed, which limits their measurement (Carlson et al, 2017). Thus, in vitro models are more suitable to study the kinetics of colonic fermentation.…”
Section: Ph Change and Ammonia Productionmentioning
confidence: 99%
“…Complex non-digestible dietary polysaccharides are thought to be degraded / fermented by colonic bacteria and affect the overall gut microbiota composition and immune function [35][36][37] , and it could impact the autoimmune outcomes. Therefore, we determined the impact of prolonged oral treatment of NOD mice with YBG on gut microbiota.…”
Section: Prolonged Oral Administration Of Low-dose Ybg Results In Chamentioning
confidence: 99%
“…Inulin, a natural dietary prebiotic found in plants, can alleviate celiac disease, diet‐induced obesity (Nicolucci et al., ), insulin resistance (Weitkunat et al., ), and abnormal elevated serum triglycerides and cholesterol levels (Lin et al., ; Martínez‐Abundis et al, ) via modulating gut microbiota, promoting the growth of a series of probiotics involving Bifidobacterium (Nicolucci et al., ; Vandeputte, ), Anaerostipes , Collinsella (Carlson et al., ), and Lactobacilli (Dewulf et al., ). Inulin also has been proved to control the inflammation in human with type 2 diabetes mellitus (Dehghan et al., ; Roshanravan et al., ).…”
mentioning
confidence: 99%